The intracellular proteome of the gut bacterium Bacteroides thetaiotaomicron is widely unaffected by a switch from glucose to sucrose as main carbohydrate source. Issue 22 (11th August 2022) - Genth, Jerome; Kaleja, Patrick; Treitz, Christian; Schäfer, Kathrin; Graspeuntner, Simon; Rupp, Jan; Tholey, Andreas
Abstract: Bacteroides thetaiotaomicron is a gram negative bacterium within the human gut microbiome that metabolizes a wide range of dietary and mucosal polysaccharides. Here, we analyze the proteome response of B. thetaiotaomicron cultivated on two different carbon sources, glucose and sucrose. Two quantitative LC‐MS based proteomics approaches, encompassing label free quantification and isobaric labeling by tandem mass tags were applied. The results obtained by both workflows were compared with respect to the number of identified and quantified proteins, peptides supporting identification and quantification, sequence coverage, and reproducibility. A total of 1719 and 1696 proteins, respectively, were quantified, covering 35 % of the predicted B. thetaiotaomicron proteome. The data show that B. thetaiotaomicron widely maintains its intracellular proteome upon change of the carbohydrates and that major changes are observed solely in the machinery necessary to make use of the carbon sources provided. With respect to the central role of carbohydrates on gut health these data contribute to the understanding of how different carbohydrates contribute to shape bacterial community in the gut microbiome. All proteomics raw data have been uploaded to the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD033704.